Methods of isolation and identification of nontuberculous mycobacteria from environmental samples: A scoping review. (January 2023) - Marshall, Julia E.; Gebert, Matthew J.; Lipner, Ettie M.; Salfinger, Max; Falkinham III, Joseph O.; Prevots, D. Rebecca; Mercaldo, Rachel A.
Abstract: Nontuberculous mycobacteria (NTM) are ubiquitous in the environment. Some species of NTM are pathogenic and cause lung disease in susceptible persons. Epidemiologic studies of environmental NTM infection risk rely on both culture-dependent and culture-independent techniques for NTM isolation and identification. In this review, we summarized current methods used to isolate and identify NTM from the environment. We searched PubMed, Embase, Scopus, Web of Science: Core Collection, and Global Health (CAB Direct) for peer-reviewed studies from the last 12 years. We identified 1685 unique citations and 110 studies met our inclusion and exclusion criteria. Approximately half (55%) of the studies identified in this review used a combination of culture-independent and culture-dependent methods. The most common environmental substrate analyzed was water (n = 90). Identification of current, common methods for the isolation and identification of NTM from environmental samples may contribute to the development of standard methodological practices in the future. The choice of isolation method is based on the research question, environment, and species. A summary of common methods may contribute to the development of standard practices for isolation and identification of NTM from environmental samples, which may lead to more robust and comparable results.